Modern weapons and military equipment for issue 3-2024 - Vučković, Dragan M. (Vojnotehnički glasnik / Military Technical Courier, 2024)
AIM-174 Super Hornet-Launched Variant Of SM-6 Missile Breaks Cover In Hawaii (Updated) Russia’s Rubezh-M coastal missile system ready to sink enemy ships up to 5,000 tons